Design of a Hydraulic Plate Bending Machine - Ismet Eka Putra; Khalid Ahsanul K (Jurnal Teknik Mesin, 2021)
This study aims to analyze the design and specifications of a plate bending machine using hydraulic power based on the bending force of the selected plate dimensions. The method used in this research is to use a computational method known as Finite Element Analysis (FEA) with the help of the Stress Analysis feature of the Autodesk Inventor 2019 Software. The dimensions of the machine frame are 1600 mm in length, 600 mm in width and 1200 mm in height. Based on the bending force on the mild steel plate with a length of 500 mm and a thickness of 2 mm, namely 5750 N, the hydraulic system planning is a hydraulic power of 0.24 kw, a pump capacity of 6,475 cc / rev and the pressure received by the cylinder is 18,488 bar. Based on the load that occurs when the bending process occurs, both in the form of bending forces, loads from bender, clamp and loads from hydraulic. The results show that the bending of the court with a length of 500 mm and a thickness of 2 mm, the machine has a safety factor value of 1.323.